Evaluating cholera vaccine effectiveness in Harare Western District amidst a new outbreak, 2023 - Mwashita, Mary Munashe; Hove, Innocent; Juru, Tsitsi; Chitiyo, Farai Josphas; Chadambuka, Addmore; Shambira, Gerald; Gombe, Notion; Mandozana, Gibson; Tshimanga, Mufuta (Intelektual Pustaka Media Utama, 2025)
Following targeted oral cholera vaccination (OCV) in 2018/2019, cholera cases declined. However, by July 17, 2023, Harare Western district reported 98 cases and 3 deaths. We investigated the outbreak to assess the long-term effectiveness of OCV in Harare Western district. We conducted a 1:2 unmatched case-control study among 46 cases and 92 controls. A case was any resident of Harare Western district with laboratory-confirmed cholera infection between April 22, - July 20, 2023. Antimicrobial susceptibility data were analyzed and multivariable logistic regression identified independent factors. Vaccine effectiveness was calculated as (1-OR) x 100). OCV effectiveness was 72o% (95% CI 39-87; p<0.001). The majority of participants were females (52.2%) cases and 51.1% controls. Experiencing a sewage burst [aOR 9.75, 95% CI (2.60 to 36.62)] was an independent risk factor. Handwashing with soap [aOR 0.03,95% CI (0.01 to 0.17)], cholera vaccination [aOR 0.17, 95% CI (0.04 to 0.64)], and having a handwashing facility [aOR 0.04, 95% CI (0.01 to 0.18)] were independent protective factors. A total of 47.2% of boreholes (42/89) and 66.7% of wells (2/3) had excessive coliforms. Cholera strains were largely sensitive to ciprofloxacillin (90%). The outbreak was driven by water, sanitation and hygiene factors. This study provides evidence on long-term effectiveness of two-doses of OCV in an endemic urban setting. Vaccination status relied on participant recall and vaccination cards due to the absence of a central register, and while the study was sufficiently powered to assess the effectiveness of the two-dose regimen, the number of cases limited evaluation of single-dose effectiveness. Implementation of targeted OCV campaigns is recommended.